A Statistical Evaluation of the Cause-Effect Relationship Between Money and Income - Ireland, M. Edwin (Journal of Finance, 1975)
Significance Tests of the Future and Past Lag Partitions for Regressions Based on Real GNP, Ml, M2, and MB 10 8 8. Tests of the Homogeneity of Coefficients for Regressions Based on Real GNP and Ml, M2, and MB 110 9. Summary of OLS and JLS Regressions Based on the GNP Price Deflator, Ml, M2, and MB ... .Ill 10.Significance Tests of the Future and Past Lag Partitions for Regressions Based on the GNP Price Deflator, Ml, M2, and MB 112 11.Tests of the Homogeneity of Coefficients for Regressions Based on the GNP Price Deflator and Ml, M2, and MB 113 V CHAPTER I